Design and Optimization of Hydraulic Control Systems for Geothermal Flow Control Valve Stability - Alfian Rangga Pradhivatama; Syah Alam (Universitas Medan Area, 2026)
Operational instability in Flow Control Valves (FCV) within Geothermal Power Plant (GPP) Circulating Water Systems (CWS) presents a significant challenge, leading to control hunting, elevated condenser levels, and degraded vacuum pressure, thereby compromising overall thermal efficiency. This study presents a systematic optimization of the FCV's Hydraulic Power Unit (HPU) control system, integrating Programmable Logic Controller (PLC) and Distributed Control System (DCS) frameworks. The methodology encompassed a comprehensive intervention involving: (1) meticulous tuning of PI control parameters, (2) mechanical and hydraulic refurbishment of the HPU, and (3) precise calibration of the 4-20 mA instrumentation signal. Post-implementation analysis revealed a profound enhancement in system stability. FCV deviation variance was drastically reduced from 0.87 to 0.20. This stabilization directly correlated with improved plant performance, evidenced by a 16% reduction in condenser level variance and an enhancement of the mean condenser vacuum from -0.73 to -0.74 bar. The findings demonstrate that this integrated PLC/DCS-based optimization provides a robust and effective solution for mitigating hydraulic control instability, enhancing CWS reliability, and improving the thermal efficiency of geothermal power generation